2023
DOI: 10.2460/ajvr.23.01.0014
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response over time correlated with treatment outcome in 30 dogs naturally infected with Brucella canis (2017–2022)

Abstract: OBJECTIVE Brucella canis is a zoonotic bacterial pathogen of dogs that is notoriously difficult to diagnose and treat. Humans can become infected with B canis when an infected pet dog is brought into their home. Our objectives were to describe the clinical presentation and outcomes in dogs treated for B canis and evaluate the performance of the quantitative serologic canine Brucella multiplex (CBM) assay for monitoring treatment response. ANIMALS Diagnostic records from the Animal Health Diagnostic Center at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…Signalment data pertaining to B canis is limited, with no strong evidence of a specific breed predisposition (Weber andSchliesser 1975, Santos andothers 2021). Sex representation is likely biased as the high-stakes nature of canine abortions prompts aggressive diagnostic investigation in bitches (Santos and others 2021), whereas meaningful data on male dogs is complicated by the prevalence of subclinical carriers (Greene 2006).…”
Section: Aetiology and Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Signalment data pertaining to B canis is limited, with no strong evidence of a specific breed predisposition (Weber andSchliesser 1975, Santos andothers 2021). Sex representation is likely biased as the high-stakes nature of canine abortions prompts aggressive diagnostic investigation in bitches (Santos and others 2021), whereas meaningful data on male dogs is complicated by the prevalence of subclinical carriers (Greene 2006).…”
Section: Aetiology and Epidemiologymentioning
confidence: 99%
“…Despite sparse literature, B canis is a well-accepted infectious cause of intraocular disease (Ledbetter andothers 2009, Vinayak andothers 2004). Clinical features of B canis ocular disease include anterior uveitis (unilateral and bilateral), panuveitis, endophthalmitis, retinal detachment and intraocular haemorrhage (Greene 2006). One paper reported that of 313 dogs confirmed with B canis, 14 per cent had ocular involvement and overall the prognosis for vision was guarded (Vinayak and others 2004).…”
Section: Ocular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In theory, it is possible to treat affected animals with a prolonged combined antibiotic therapy (Graham et al, 2022;Greene & Carmichael, 2012;Guarino et al, 2023), but it is mandatory to F I G U R E 1 Ultrasonographic aspect of an embryonic resorption 24 days post-ovulation in a bitch (© A Fontbonne).…”
Section: Canine Brucellosismentioning
confidence: 99%
“…In theory, it is possible to treat affected animals with a prolonged combined antibiotic therapy (Graham et al, 2022; Greene & Carmichael, 2012; Guarino et al, 2023), but it is mandatory to sterilize, remove them from the kennel and inform the new owners about the zoonotic risk, especially for children, old people and immunosuppressed persons. Indeed, recovery is never guaranteed, even if a seronegativity is restored, and relapses are frequent.…”
Section: Bacterial Causes Of Pregnancy Arrestmentioning
confidence: 99%